Impact of Epstein-Barr virus load, virus genotype, and frequency of the 30bp deletion in the viral BNLF-1 gene in patients harboring the human immunodeficiency virus - Giron, Leila Bertoni [UNESP]; Ramos da Silva, Suzane [UNESP]; Barbosa, Alexandre Naime [UNESP]; Monteiro de Barros Almeida, Ricardo Augusto [UNESP]; Rosário de Souza, Lenice do [UNESP]; Oliveira, Deilson Elgui de [UNESP] (Wiley, 2013)
Patients infected with the human immunodeficiency virus (HIV) are at higher risk of developing Epstein-Barr Virus (EBV)-associated lymphomas. The usefulness of monitoring EBV in peripheral blood mononuclear cells (PBMCs) of patients infected with HIV has not been established. The aim of this study was to evaluate the EBV viral load in PBMCs, the frequency of viral genotypes, and the presence of the 30-bp deletion in the BNLF-1 gene. DNA samples from 156 patients attending the HIV/AIDS Day Clinic at Botucatu School of Medicine, Sao Paulo State University were evaluated. The EBV viral load was detectable by real time PCR in 123/156 (78.8%) cases and was higher in patients not receiving antiretroviral treatment or under therapeutic failure than in patients under successful highly active antiretroviral therapy (HAART) (P=0.0076). Overall, the profile of patients with high EBV viral load included elevated HIV viremia (P=0.0005), longer time of HIV diagnosis (P=0.0026), and increased levels of T CD8 + lymphocytes (P=0.0159). The successful amplification of the EBNA-2 gene by nested-PCR was achieved in 95 of 123 (77.2%) cases, of which 75.8% were EBV-1, 9.5% EBV-2, and 14.7% were co-infected with both EBV-1 and -2. The analysis of the BNLF-1 gene was possible in 99 of 123 (80.5%) cases, of which 50.5% had the 30-bp deletion. EBV-1 was more common than EBV-2, which may reflect the fact that the cohort was predominantly Caucasian and heterosexual. J. Med. Virol. 85:2110-2118, 2013. © 2013 Wiley Periodicals, Inc.
Keywords: Molecular biology; Prospective study; Viral carcinogenesis; Viral co-infection